(untitled) (Scientific journal of the Fergana State University, 2025)
The article considers the creative potential of teachers undergoing professional development as the main issue, the development of their professional and personal qualities, the causes and solutions to the problems encountered during their work. For these reasons, methods and recommendations are presented that will help to further develop the personal and creative potential of teachers undergoing professional development, including the art of establishing dialogue with others, initiative in establishing value relations in various fields, social activity in knowledge and activity, and continuous professional skills.